(untitled) (lectio difficilior, 2009)
The main question of this article is, in which spaces or places women live according to Old Testament texts. As a result of a close reading of the whole Old Testament, over one hundred text passages can be found, where women are placed in a space which is mentioned in the text. These passages can be divided into two main groups: on the one hand those referring to settlements and on the other hand those referring to nature (the world outside the settlement). In this article a closer view is given on text passages referring to settlements like e.g. houses, palaces and cities.